Canadian building contracts - Goldsmith, Immanuel (Canada : The Carswell Company Ltd., 1983)
The second edition of this book, which appeared some seven years ago, is out of print, and a third edition is offered in the hope that it will fulfil an existing demand.
Chapter 1. The contract -- Chapter 2. The terms -- Chapter 3. Performance -- Chapter 4. Payment -- Chapter 5. Breach of contract -- Chapter 6. Remedies for breach -- Chapter 7. Sub-contractors -- Chapter 8. Architects and engineers -- Chapter 9. Bonds -- Chapter 10. Arbitration -- Chapter 11. Mechanics' Lens.
Includes index.
Keywords: BUILDING -- CONTRACTS AND SPECIFICATIONS -- CANADA